EFEKTIFITAS PENDEKATAN STEM DALAM PRAKTIKUM IPA MELALUI EKSPERIMEN SEDERHANA: SIFAT-SIFAT CAHAYA UNTUK MENINGKATKAN KEMAMPUAN CRITICAL THINKING SISWA KELAS VB DI SDN 192 PEKANBARU - Dwi Sentia; Samsul Bahtiar; Sintia Rahmadhani; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of the STEM (Science, Technology, Engineering, and Mathematics) approach in science practicum through simple experiments on the properties of light to improve the critical thinking skills of fifth-grade elementary students. The background of this research is the low level of students’ critical thinking skills, which is influenced by less innovative learning processes and the abstract nature of science concepts, particularly light properties. This study employed a pre-experimental design using a one-group pretest-posttest design. The subjects were 25 students of class VB at SDN 192 Pekanbaru. Data were collected through tests, observations, and documentation. The instruments included multiple-choice questions to measure critical thinking skills before and after the implementation of the STEM-based practicum. Data analysis was conducted using descriptive and inferential statistics, including normality tests, paired sample t-tests, and N-Gain analysis. The results showed that the average pretest score was 63.2 (moderate category), while the posttest score increased to 74.4 (good category). The N-Gain score was 0.3, indicating a moderate level of improvement. Furthermore, the paired t-test results showed a significance value (p < 0.05), indicating a significant difference between pretest and posttest scores. Therefore, it can be concluded that the STEM approach in science practicum through simple experiments on light properties is effective in improving students’ critical thinking skills. This approach not only enhances conceptual understanding but also encourages active learning, problem-solving, and analytical thinking.